Assessing Mean Change in Retinal Nerve Fiber Layer Thickness on Optical Coherence Tomography in Glaucoma Patients after Trabeculectomy - Khizir Hayat; Muhammad Younis Tahir; Muhammad Ajmal Chaudhary; Adeel Ahmad Siddiqui; Sadia Haneef (Pakistan Journal of Medical Research)
Background: Glaucoma leads to changes in visual fields, optic nerve head (ONH) and retinal nerve fiber layer (RNFL). It is important to detect glaucomatous damage to avoid visual impairment and initiate treatment. Reversal of glaucomatous damage after intraocular pressure (IOP) lowering treatments has been reported in glaucoma patients. ONH and RNFL imaging by optical coherence tomography (OCT) are important to evaluate anatomical changes in glaucoma patients.